Maturity level of rural leaders in selected paddy farming technologies in Muda Agricultural Development Authority (MADA)-Malaysia - Masso, Wisam Yako Aziz; Man, Norsida (Canadian Center of Science and Education, 2016)
To provide good leadership it is necessary for individuals and groups to help bring a rural community to action. As the rural leaders play a function in important programs in agricultural extension. However, The study was conducted to determine the maturity of rural leaders based on maturity model theory towards agricultural technologies In Malaysia Paddy Farming, and explore the relationship between the selected characteristics of the respondents. Data were collected through personal interview from 260 randomly selected in muda agriculture development authority MADA area. A five point Likert scale was used to determine the maturity of rural leaders ranged from 1 = never to 5= always.The majority (63.1%) of the respondents had a moderate level of maturity. The correlation analysis between socio-demographic characteristics and maturity level show that there is a positive and significant relationship between variables age and years of experience in paddy farming, at 0.05 level of significance.